Protecting Traditions with Modernization: Community Empowerment in Rejowinangun through the Village of Traditional Herbal Medicine Destination - Sriharini Sriharini; Shofwah Syafira (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2020)
This article aims to provide another perspective on the concept of community empowerment by utilizing local potential with cultural value combined with a tourism-based empowerment pattern. Herbal medicine as a hereditary heritage in Rejowinangun village is optimized for marketing in the concept of a tourist village, thereby increasing its economic value in a modern society. To achieve this goal, this study uses a qualitative method with a phenomenological approach to capture the context of changes experienced by the community to see the significance of the empowerment model. The results of this study indicate that the process of developing the production of herbal medicine as a processed product of herbal plants is produced through the use of land owned by the community. The expertise of the Rejowinangun village community in concocting traditional herbal medicine is produced from hereditary inheritance. As a form of re-actualization in the marketing system, modern methods were introduced, from the concept of a tourist village to marketing herbal medicine in the form of instant packaging. Modernization steps in all aspects as part of empowerment have an impact on increasing the economic value of these products, so that they have an impact on improving the community in the economic, social, cultural, environmental and health fields. The integration between the concept of cultural preservation and modern management in community development that takes place in the village of Rejowinangun has proven to be effective and efficient, so that this method can be a new alternative in group-based community development that still preserves local traditions and keeps up with the times.